Agents unleased : a public domain look at agent technology - Wayner, Peter, 1964- (AP Professional, 1995)
Agents Unleashed: A Public Domain Look at Agent Technology covers details of building a secure agent realm. The book discusses the technology for creating seamlessly integrated networks that allow programs to move from machine to machine without leaving a trail of havoc; as well as the technical details of how an agent will move through the network, prove its identity, and execute its code without endangering the host. The text also describes the organization of the host's work processing an agent; error messages, bad agent expulsion, and errors in XLISP-agents; and the simulators of errors, functions, and resources. Agent language, XLISP, TCL and other languages are also considered. The book further tackles security and encryption; commercial cash; and some ambitious and extreme examples of how people are attempting to create agents. The text also encompasses the instructions on how to use the XLISP agents. Software agents will find the book invaluable.